Pengaruh Pemimpin Terhadap Keberhasilan Penanaman Gereja Menurut Buku Kisah Para Rasul - Pany, Yohanes Gijs (Jurnal Salvation, 2024)
Abstract: Leadership is the key to the progress of an institution, including the church as a ministry institution. Weak church leadership will have a negative impact on church development. The early church, which the book of Acts states is a model for today's church in terms of its growth strategies, Theologically, the growth of the early church was the work of the Holy Spirit pouring out His power. The book Acts 1:8 expresses it this way: "But you will receive power when the Holy Spirit has come upon you, and you will be My witnesses in Jerusalem and in all Judea and Samaria and to the ends of the earth.". However, in terms of management and ministry of the church as an institutional organization, of course, the 'leadership' carried out by the Apostles can also be a model for church leadership today.